Overview of Nutritional Status, Breakfast Habits, and Nutritional Knowledge among University Students - Syaima, Afaf; Wulandari, Dewi Yully; Gandini, Intan; Nisa, Hoirun (Epidemiology and Society Health Review (ESHR), 2025)
Background: Nutrition-related issues can lead to increased morbidity and mortality, with a rising prevalence of malnutrition among young adults. Breakfast habits and nutrition-related knowledge significantly influence an individual's nutritional status. This research aims to describe breakfast habits,  nutritional knowledge,  and nutritional status among students of the Faculty of  Health  Sciences at  UIN  Syarif  Hidayatullah Jakarta from 2020 to 2022. Method: This was a quantitative study that employed a cross-sectional. The study includes 469 students from the Faculty of Health Sciences at UIN Syarif Hidayatullah Jakarta, selected through stratified random sampling based on the year of admission. Data were analyzed using univariate methods to observe the frequency distribution of nutritional status, breakfast habits, and nutrition knowledge among the students. Results: The findings indicate that a significant proportion of students have underweight nutritional status (30.3%), engage in irregular breakfast habits (56.7%), and consume breakfast after 9:00 AM (44.8%). Additionally, many students do not include staple foods in their breakfast (45.2%) and lack sufficient nutrition knowledge (43.9%). Conclusion: The study reveals ongoing nutritional challenges among students, including underweight status and obesity. Corresponding with these issues, some students exhibit irregular breakfast habits and delay breakfast until after 9:00 AM. Furthermore, 45.2% of students omit staple foods from their breakfast, and 43.9% possess inadequate nutrition knowledge. Future research should explore the relationship between breakfast habits, nutrition knowledge, and individual nutritional status to provide more comprehensive insights.